Strategi Pengembangan Produk Untuk Menciptakan Keberlanjutan Pemasaran Pada Perusahaan Farmasi Multinasional - Sari Wijayanti; Triana Hasty Kusuma; Stevi Jimry Poluan; Rizka Fatkhin Nisa (AKSIOMA : Jurnal Manajemen, 2025)
The purpose of this research is to find out how product development strategies contribute to creating marketing sustainability in multinational pharmaceutical companies. This study was conducted using a qualitative approach (case study) using two key informants, namely a Country Medical Affairs Head and Product Manager from a multinational pharmaceutical company ‘X’ in Indonesia, and conducted in-depth interviews, data triangulation, and secondary data collection. The result of this study is the existence of clinical and commercial development in multinational pharmaceutical companies to create marketing sustainability by emphasizing strategy evaluation and product sustainability.